Microbicides for Topical HIV Immunoprophylaxis: Current Status and Future Prospects - Yury V. Zhernov; Vladislava O. Petrova; Mark Y. Simanduyev; Denis V. Shcherbakov; Roman V. Polibin; Oleg V. Mitrokhin; Artem A. Basov; Nadezhda N. Zabroda; Sonya O. Vysochanskaya; Ezzulddin Al-khaleefa; Kamilla R. Pashayeva; Narmina Yu. Feyziyeva (MDPI AG, 2024)
Microbicides, which are classified as topical antiseptic agents, are a revolutionary advancement in HIV prevention aimed to prevent the entry of infectious agents into the human body, thus stopping the sexual transmission of HIV and other sexually transmitted diseases. Microbicides represent the promise of a new age in preventive measures against one of the world's most pressing health challenges. In addition to their direct antiviral effects during HIV transmission, microbicides also influence vaginal mucosal immunity. This article reviews microbicides by presenting different drug classifications and highlighting significant representatives from each group. It also explains their mechanisms of action and presents information about vaginal mucosal immune responses, emphasizing the critical role they play in responding to HIV during sexual transmission. The article discusses the following groups of microbicides: surfactants or membrane disruptors, vaginal milieu protectors, anionic polymers, dendrimers, carbohydrate-binding proteins, HIV replication inhibitors (reverse transcriptase inhibitors), and multi-purpose prevention technologies, which combine protection against HIV, other sexually transmitted diseases, and contraception. For each chemical compound, the article provides a brief overview of relevant preclinical and clinical research, emphasizing their potential as microbicides. The article offers insights into the multifaceted impact of microbicides, which signify a pivotal step forward in the pursuit of effective and accessible pre-exposure prophylaxis (PrEP).